On the Regressivity of Gambling Taxes in Switzerland - Dimitri Kohler (Swiss Journal of Economics and Statistics, 2016)
In this study, the author assesses whether the gambling tax in Switzerland is regressive using a large, representative sample of the population and the reported gambling expenditures of the Swiss Health Survey 2007 (SHS 07). To analyze the tax incidence, the Suits index was constructed. This result is supported by a regression analysis, which highlights the income elasticity of gambling expenditures. The two measures provide converging results and demonstrate the regressive pattern of the gambling tax in Switzerland. As such, this taxation structure contributes to increased income inequality in Switzerland.
Keywords: H22; D63; I14; I18; 330; gambling taxes; inequity; regressivity; incidence